Avaliação da atividade antinociceptiva da talidomida, pentoxifilina e clorpromazina em modelos experimentais - Vale, Mariana Lima (2003)
The release of cyclo-oxygenase products and sympathomimetic amines, the final mediators of inflammatory pain, is preceded by the generation of pro-inflammatory and nociceptive cytokines by resident cells. Recently drugs such as thalidomide (TALD), pentoxifylline (PTX) and chlorpromazine (CLP), despite of other effects, have been associated with immunomodulatory activity in clinical practice mainly for their modulatory properties upon cytokine production. Since those drugs are able to inhibit the production of pro-inflammatory cytokines and the pivotal role of resident cells in the development of inflammatory pain we have decided to test the possibility of TALD, PTX and CLP, to modulate inflammatory pain. TALD (5 – 45mg/kg), PTX (0.5 – 45mg/kg) or CLP (0.1 – 1mg/kgl) was given 30 min before either acetic acid (AAc) or zymosan (Zym) or iloprost (ILO) administration in the writhing model. TALD, PTX or CLP, at the same doses were injected, i.p., 30 min before Zym (1 mg/animal; intra-articular) in the zymosan-induced rat knee joint incapacitation test (JI). Those drugs were also tested upon hyperalgesic effect of carrageenin (Cg), bradykinin (Bk), tumor necrosis factor (TNF), interleukin (IL) -1 and prostaglandin E2 (PGE2) on mechanical hyperalgesia test (HYP). Doses of those drugs that exerted maximum effect in the writhing test were also injected 30 min before the hot plate test. These same doses were injected ip before naloxone administration in the AAc-induced writhing model in mice. Cytokines levels (TNF, IL-1, IL-10 and IL-4) were determined in the supernatant of a macrophage culture, which were collected from peritoneal fluid of mice treated with Zym and pre-treated with the drugs under test and in the supernatant of articular fluid of rats pre-treated with the drugs and stimulated with Zym (TNF, IL-1 beta, IL-10, IL-6 and CINC-1). Our results showed that TALD, PTX and CLP inhibited the writhing response in mice induced by AAc or Zym up to 60.3, 89.8 e 89%, and up to 85.6, 82.9 and 63.7% respectively (p<0.001), but not the nociceptive response to ILO. Similar results were observed in the JI induced by Zym: 75, 89 e 99% of inhibition, respectively (p<0.01). TALD inhibited hyperalgesic effect of Cg (78.6%) and Bk (82.4%), but not the hyperalgesic effect of TNF or PGE2. PTX inhibited Cg, TNF or Bk-induced HYP in 73.3, 55.2 and 45.6% of inhibition respectively, but not IL-1 or PGE2 hyperalgesic activity. CLP inhibited a hyperalgesic effect of all stimuli in different levels (68.16, 58.5, 42, 38.8 and 21.1% of inhibition for Cg, Bk, TNF, IL-1 e PGE2, respectively). The antinociceptive activity of TALD, PTX and CLP seems to be peripheral, since these drugs presented no effect in the reaction time of the animals on hot plate test. This antinociceptive effect seems to have no relation with endogen opioid release since naloxone (opioid receptor antagonist) had no effect in reverting the antinociceptive effect of these drugs in the Zym-induced writhing in mice. The antinociceptive activities seems to be dependent of the release inhibition of pro-nociceptive cytokines by resident cells since TALD, PTX and CLP inhibited the release of TNF (100, 85 e 54.4%, respectively - p<0.005) and of IL-1 (97%, PTX effect - p<0,01) by mice peritoneal resident cells as well as the production of both TNF (77 e 87.5% by TALD and PTX respectively) and IL-1 (47 e 32.6% by PTX and CLP, respectively) in the articular cavity of ZYM stimulates rats.